Principles for the design of a history and heritage game based on the evaluation of immersive virtual reality video games. (July 2021) - Egea-Vivancos, Alejandro; Arias-Ferrer, Laura
The extension of technology in current society has encouraged teachers to introduce products based on VR and IVR in their classrooms, especially video games. In this paper the specific role of video games in cultural heritage and history teaching is analyzed. Moreover, the results of recent research on the application of video games in Secondary Education is discussed. The results advocate taking into account principles such as Civic Education, Historical Relevance, Engagement, Applicability and Multimodality (what has been called the CREAM Model) in the design of a video game. These principles are especially important if the video game aims to introduce archaeological and/or historical contents into the classroom. This model has been implemented in the design of the IVR video game Carthago Nova, which is discussed as an exemplar of how the proposed principles can be engaged. The educational sequence, in which the video game is contextualized, reinforces its educational aims.